Population structure, site fidelity, and fine-scale habitat use of the broadnose sevengill shark, Notorynchus cepedianusat Pyramid rock, False Bay, South Africa - Raw, Robert Nicolas Vause (Department of Oceanography, 2015)
Includes bibliographical references.